1984
DOI: 10.2135/cropsci1984.0011183x002400020044x
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of the Digital Fibrograph Length Uniformity Index1

Abstract: The Digital Fibrograph length uniformity index is usually misinterpreted. The theoretical maximum for this index is 51.28. The theoretical maximum index requires that: 1) all cotton (Gossypium sp.) fibers within the beard being scanned by the Fibrograph have the same length, 2) that the fibers are randomly caught and held, and 3) that the optical scan of the beard begin at the point of holding. The latter condition does not exist, because the scan of the beard begins at 3.81 mm from the point of holding. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The portion of the fiber beard going from the edge of the comb to the scanning starting point is 3.81 mm (0.15 inch) long and is the same for all Uster HVIs. [21][22][23] Values are expressed as distances and not lengths because the starting offset distance is not included for analysis in this research. However, this is a constant offset and including it should not change the presented results.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The portion of the fiber beard going from the edge of the comb to the scanning starting point is 3.81 mm (0.15 inch) long and is the same for all Uster HVIs. [21][22][23] Values are expressed as distances and not lengths because the starting offset distance is not included for analysis in this research. However, this is a constant offset and including it should not change the presented results.…”
Section: Methodsmentioning
confidence: 99%
“…Before measurement, the beard is brushed to remove loose fibers and trash particles. The beard is then scanned over a light source starting 3.81 mm away from the base of the comb to the end of the fiber sample, 21,22 and a receiver on the opposing side of the beard is used to measure the amount of light attenuated by the beard. The starting point of the scanning of the beard is the maximum point of light attenuation and is used to standardize the measurement to 100%.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The additional correction for start of scan tends to increase the Ul by about 20% to 25% for these data. This increase has been explained [ 3 ] as primarily due to the increase in the 50% span length. The adjustment due to estimated crimp change the UI slightly.…”
Section: Crimpmentioning
confidence: 99%
“…, Hertel [ 2 considered the factors affacting fiber length-scanning measurements and concluded that fiber crimp, fiber-end taper, and lack of random damping were the important causes. We have reconsidered the factors affocting fiber length measures and concluded that fiber crimp, lack of random clamping, start of scan [3], lens width [4], fiber taper, and holding length are the factors affecting fiber length-scanning measurements. We believe that fiber taper causes a proportionate but minimal affect tending toward longer lengths, since more fibers end close to the holding element than towards the edge of the beard.…”
mentioning
confidence: 99%